JUDOKAS ANAEROBIC CAPACITY ASSESSMENT (Fiep Bulletin - online, 2011)
This study sought to evaluate the performance of judo athletes in an anaerobic task. The test was composed of four sets of wingate for upper limbs with an interval of 3 minutes between sets. For each series were determined relative mean power (RMp) and relative peak power (RPp). The sample was intentionally convenience, it was composed of 09 judo male, aged between 14 and 26 years old. The results showed that the judoka showed a low anaerobic performance. Regarding the relative peak power, it was indicated that the 3-minute recovery interval were sufficient to make recovery ability. The post-test heart rate should be improved to better cardiovascular efficiency for the same effort.
Keywords: judo; anaerobic power; motor performance